Efficacy and safety of sacubitril/valsartan after switching from azilsartan in hemodialysis patients with hypertension - Yoshio Iwashima; Hiromichi Fukushima; Takeshi Horio; Tatemitsu Rai; Toshihiko Ishimitsu (The Journal of Clinical Hypertension, 2023)
Abstract This study assessed the efficacy and safety of sacubitril/valsartan in 23 hemodialysis patients with hypertension (mean age 70 years; male 69.6%) after switching from azilsartan, an angiotensin receptor blocker. Both at baseline and 3 months after the start of sacubitril/valsartan treatment, home blood pressure (BP), BP values during hemodialysis, and N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) level were measured. The mean dosage of azilsartan was 30 ± 10 mg/day at baseline and that of sacubitril/valsartan after 3 months of treatment was 204 ± 64 mg/day. After 3 months, significant reductions in mean morning home BP (155 ± 17/80 ± 12 to 147 ± 16/76 ± 11 mmHg), mean nighttime home systolic BP (153 ± 19 to 144 ± 16 mmHg), and median (IQRs) NT‐proBNP level [8124 (2620–13 394) to 6271 (1570–9591) pg/mL] were observed (all P < .05), whereas BP values during hemodialysis did not change significantly. In hemodialysis patients, except for hypotension, sacubitril/valsartan was generally well tolerated, effectively controlled out‐of‐office BP, and improved NT‐proBNP.